2021
DOI: 10.3390/biomedicines9020119
|View full text |Cite
|
Sign up to set email alerts
|

HuR Protein in Hepatocellular Carcinoma: Implications in Development, Prognosis and Treatment

Abstract: Hu-antigen R (HuR) is a post-transcriptional regulator that belongs to the embryonic lethal abnormal vision Drosophila-like family (ELAV). HuR regulates the stability, translation, subcellular localization, and degradation of several target mRNAs, which are implicated in carcinogenesis and could affect therapeutic options. HuR protein is consistently highly expressed in hepatocellular carcinoma (HCC) compared to the adjacent normal liver tissue and is involved in the post-transcriptional regulation of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…These results demonstrated that ADORA2A-AS1 specifically bound to HuR. HuR is reported to bind and stabilize several mRNAs, including FSCN1, VEGFC, MAT2A, MDM2, CCND1, CASP3, USP7, FAS, PDGFA, CTSS, GATA3, and EGFR (41)(42)(43)(44)(45)(46). The RNA-seq data of HCC tissues from TCGA project showed that among all these HuR targets, FSCN1 has the most significant correlation with ADORA2A-AS1 with r value of -0.4627 (Figure 5C and Figure S2).…”
Section: Adora2a-as1 Downregulated Fscn1 Via Binding Hurmentioning
confidence: 73%
See 2 more Smart Citations
“…These results demonstrated that ADORA2A-AS1 specifically bound to HuR. HuR is reported to bind and stabilize several mRNAs, including FSCN1, VEGFC, MAT2A, MDM2, CCND1, CASP3, USP7, FAS, PDGFA, CTSS, GATA3, and EGFR (41)(42)(43)(44)(45)(46). The RNA-seq data of HCC tissues from TCGA project showed that among all these HuR targets, FSCN1 has the most significant correlation with ADORA2A-AS1 with r value of -0.4627 (Figure 5C and Figure S2).…”
Section: Adora2a-as1 Downregulated Fscn1 Via Binding Hurmentioning
confidence: 73%
“…Previous reports have shown that high expression of HuR was associated with poor survival in HCC (45). HuR promotes HCC malignant progression via regulating several mRNA targets (45).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In MCF-7 cells also, miR-21 was shown to be sequestered by the RNA-binding protein HuR, thereby preventing mRNA decay of PDCD4 , a classical target of miR-21 [ 93 ]. Of note, HuR is strongly upregulated in human HCC, where it correlates with a poor prognosis [ 106 ]. It is now also clear that in specific pathological situations mRNAs targeting by miR-21 is likely a matter of a delicate stochiometric equilibrium depending on the amount of miR-21 available, the amount of mRNA target molecules and their competition to bind miR-21, as well as the titration of free miR-21 by irrelevant targets or pseudogenes [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…mRNA-binding proteins are involved in the post-transcriptional deregulation of gene expression. Thus, AUF1 increases mRNA decay while HuR selectively binds to AU-rich elements increasing mRNA stability [32,[46][47][48][49]. Interestingly, Mat1A decrease, Mat1A:Mat2A switch, and low SAM levels are associated with CpG hypermethylation and histone H4 deacetylation of Mat1A promoter, and prevalent CpG hypomethylation and histone H4 acetylation of Mat2A promoter.…”
Section: The Deregulation Of Methionine Metabolism In Preneoplastic and Neoplastic Livermentioning
confidence: 99%